If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 5x = 2(x + -6) Reorder the terms: 12 + 5x = 2(-6 + x) 12 + 5x = (-6 * 2 + x * 2) 12 + 5x = (-12 + 2x) Solving 12 + 5x = -12 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + 5x + -2x = -12 + 2x + -2x Combine like terms: 5x + -2x = 3x 12 + 3x = -12 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + 3x = -12 + 0 12 + 3x = -12 Add '-12' to each side of the equation. 12 + -12 + 3x = -12 + -12 Combine like terms: 12 + -12 = 0 0 + 3x = -12 + -12 3x = -12 + -12 Combine like terms: -12 + -12 = -24 3x = -24 Divide each side by '3'. x = -8 Simplifying x = -8
| r/14=4 | | 13x+14=7x+14 | | 0=-16t+116t+101 | | 0=0.74b+1.26b-2b | | 12.8/8 | | 9x+8x-10x-5x+3x-23=15-8 | | 7a-5=2[2a-13] | | 2a(7a+5)=0 | | 18=3z+3 | | 3x+1=8-x | | -7/6y=-35 | | 60-12b-12=0 | | 3y+7y-4y-4y-8=10+4 | | 7/9+(-2/3) | | 10k-3k=7k+84 | | 0=z^2+6 | | 4/5y=40 | | 5x-7x=10x+8 | | -2-4x=10 | | y^2+5=5 | | 12-6p=24+6p | | 50x+5=10x | | 2x+6+42= | | -24+8x=6x-4(x-6) | | 6t(11+5)=0 | | 5-3x=-10 | | 3x+4x+5x-8x+8=12 | | b^2=100 | | -3(1t+5)+(4t+2)=8 | | x=-2(80)+300 | | 4(10x-7)=292 | | 7p-4=1-3p |